Pengembangan Modul Pembelajaran Anatomi dan Fisiologi Manusia Berbasis Studi Kasus (Case Study) untuk Mahasiswa Prodi Pendidikan IPA UNIMED - Sri Enita Ginting; Melva Silitonga; Martina Restuati (BIOEDUSAINS:Jurnal Pendidikan Biologi dan Sains, 2025)
This study aims to develop a case-based learning module on Human Anatomy and Physiology that is feasible for use by students of the Science Education Study Program at Universitas Negeri Medan (UNIMED). The research was conducted from January to June 2025 at the Faculty of Mathematics and Natural Sciences (FMIPA), UNIMED. The method used was research and development (R&D) with the MANTAP model level 1, which includes the stages of needs analysis, product development, and validation. The research subjects included lecturers of the Anatomy and Physiology course and students from the 2023 cohort of the Science Education Study Program at UNIMED. Data were collected through questionnaires and validation sheets, and analyzed both quantitatively and qualitatively. The results show that the developed module received an “excellent” rating from the subject matter expert (89.27), instructional design expert (92.25), and graphic design expert (86.80). It was also considered “highly practical” based on feedback from lecturers (92.16) and students, both in small groups (81.9) and larger groups (83.4). In conclusion, this case-based module is highly feasible and practical as a contextual teaching material to support the learning process of Science Education students at UNIMED.   Keywords: Anatomy, Physiology, Module, Development, Case Study